Italian Oncological Pain Survey (IOPS): A Multicentre Italian Study of Breakthrough Pain Performed in Different Settings. Issue 3 (March 2015) - Mercadante, Sebastiano; Lazzari, Marzia; Reale, Carlo; Cuomo, Arturo; Fusco, Flavio; Marchetti, Paolo; Mediati, Rocco D.; Chiurazzi, Bruno; Ciuffedra, Libero; Caraceni, Augusto; Iaffaioli, Vincenzo; Luzzani, Massimo; et al.
Abstract : Objective: A survey of breakthrough pain (BTP) was performed in five palliative care units (PCU), seven oncology departments (ONC), and nine pain clinics (OPC). Methods: A standard algorithm was used to confirm the diagnosis of BTP of patients refereed to different settings. Results: 1, 412 evaluable cancer patients were enrolled. 53.9% were males and the mean age was 63.7±13.1 years. The mean intensity of background pain was 2.8±0.73. Patients reported 2.4±1.1 BTP episodes/day with a mean intensity of 7.37±1.28. 80.6% patients reported that the BTP had a significant negative impact in everyday life. The majority of patients reported a fast onset of BTP, which was predictable in 50.7% of cases, while BTP with a gradual onset (>10 min) was less predictable (29%) ( P =0.001). PCU patients were older, had lower Karnofsky levels, a lower number of BTP episodes/day, a slow onset of BTP onset, and a less predictable BTP. Cancer diagnosis was performed a mean of 23.5 months (SD±32.8) before the assessment. The mean duration of background pain was 3.5 months (SD±3.5), and the mean duration of any analgesic treatment was 2.5 months (SD±3). BTP started a mean of 2.2 months (SD±1.9) before the assessment. Characteristics of BTP were influenced by the course of disease, as well as the duration of background pain and initiation of BTP. Most patients took rapid onset opioids and were satisfied with the treatment. BTP diagnosis was prevalently made by ONC and OPC physicians, and rarely by GPs. Conclusion: This survey performed by an Italian observatory expert review group, has confirmed that the BTP represents a clinically relevant condition with a negative impact on the patient's quality of life. BTP was detected in all settings involved. A number of factors are associated with the BTP. Also factors regarding the course of disease and setting of care have been assessed. This information may help in stratifying patients or predicting the risk of development of BTP with specific characteristics.